2002
DOI: 10.1506/llth-jxqv-8cew-8mxd
|View full text |Cite
|
Sign up to set email alerts
|

Audit‐Firm Tenure and the Quality of Financial Reports*

Abstract: This study examines whether the length of the relationship between a company and an audit firm (audit‐firm tenure) is associated with financial‐reporting quality. Using two proxies for financial‐reporting quality and a sample of Big 6 clients matched on industry and size, we find that relative to medium audit‐firm tenures of four to eight years, short audit‐firm tenures of two to three years are associated with lower‐quality financial reports. In contrast, we find no evidence of reduced financial‐reporting qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
581
9
48

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 827 publications
(679 citation statements)
references
References 29 publications
41
581
9
48
Order By: Relevance
“…As Big 4 auditors are generally considered higher quality than non-Big 4 auditors (DeFond 1992;DeFond et al 2016;Palmrose 1988), clients of the Big 4 may be less likely to violate GAAP. As an additional auditor characteristic, we include auditor tenure, Auditor_Tenure, which could be associated with higher reporting quality due to auditor learning or lower reporting quality if auditor independence is compromised (Geiger and Raghunandan 2002;Johnson et al 2002;Myers et al 2003). We differentiate between auditor changes initiated by the client, Auditor_Dismissed, and those initiated by the auditor, Auditor_Resigned, to control for their potentially varying effects on our dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…As Big 4 auditors are generally considered higher quality than non-Big 4 auditors (DeFond 1992;DeFond et al 2016;Palmrose 1988), clients of the Big 4 may be less likely to violate GAAP. As an additional auditor characteristic, we include auditor tenure, Auditor_Tenure, which could be associated with higher reporting quality due to auditor learning or lower reporting quality if auditor independence is compromised (Geiger and Raghunandan 2002;Johnson et al 2002;Myers et al 2003). We differentiate between auditor changes initiated by the client, Auditor_Dismissed, and those initiated by the auditor, Auditor_Resigned, to control for their potentially varying effects on our dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Several prior studies document that a higher auditor quality (auditor size, industry specialization and tenure) mitigate the accruals earnings management (Becker et al 1998;Johnson et al 2002;Krishnan 2003;Balsam et al 2003;Myers et al 2003). But, fewer researches indicate that the higher audit quality enhance the real earnings management.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…Furthermore, empirical evidence on audit quality measures has been mixed. For example, while many existing studies show that the use of brand name (Big N) auditors reduces earnings management (Becker et al, 1998;Francis et al, 1999;Lim and Tan, 2009) many other studies show that industry specialist auditors and short tenure of audit have the abilities and incentives to detect and constrain accounting-based earnings management (Krishnan, 2003;Riechelt and Wang, 2010;Ahsen, 2011;Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (2002) also showed that discretionary accruals during the early years of auditing tenure are higher than towards the end of an auditor's tenure. Walker et al (2001) also concluded that the audit failure rate is less wherever there is a long connection between auditor and employer.…”
Section: Auditor Tenurementioning
confidence: 94%